Analysis of Maternal and Infant Risk Factors Associated with Early Breastfeeding Initiation - Pratama, Muhammad Noor Aditya; Kania, Nia; Bakhriansyah, Mohammad; Triawanti, Triawanti; Suhartono, Eko (Jurnal Berkala Kesehatan, 2024)
Early Initiation of Breastfeeding (EIB) is the process of breastfeeding a baby to his/her mother within 1 hour of delivery. Newborns with EIB in Banjarmasin decreased from 98.38% in 2020 to 42.32% in 2021 with the lowest rate found in Kuin Raya Primary Health Center by 29.8%. This study aims to discover the association between maternal factors and infant factors and EIB status in Kuin Raya Primary Health Center in 2023. This was an analytic observational study using a cross-sectional approach. Samplings were recruited by using simple random technique. All data were collected by using questionnaire distributed to respondents. Prevalence Odds Ratios (PORs) and 95% Confidence Intervals (95%CIs) were calculated by using binomial logistic regression analysis with stepwise technique. The research results show that there are p-values for LBW (p=0.002), premature birth (p=0.007), knowledge (p=0.419), age (p=0.145), parity (p=0.954) and multiple births (p =cannot be measured because 100% singleton births). The conclusion is that there is a relationship between LBW and premature birth with maternal IMD status, there is no relationship between knowledge, age, parity and multiple births with maternal IMD status. The variable most associated with maternal IMD status is LBW.